A two-sided Bernoulli-based CUSUM control chart with autocorrelated observations - S. M. T. Fatemi Ghomi; F. Sogandi (Journal of Industrial Engineering International, 2019)
Usually, in monitoring a proportion p, the binary observations are considered independent; however, in many real cases, there is a continuous stream of autocorrelated binary observations in which a two-state Markov chain model is applied with first-order dependence. On the other hand, the Bernoulli CUSUM control chart which is not robust to autocorrelation can be applied two-sided control chart to able to detect either increases or decreases in the process parameter. In this paper, a two-sided Bernoulli-based CUSUM control chart is proposed based on a log-likelihood-ratio statistic using a Markov chain model and average run length relationship. The average run length relationship is set using the corresponding upper and lower Bernoulli CUSUM charts. Simulation studies show the superior performance of the proposed monitoring scheme. Numerical results show the superior performance of the proposed control chart.
Keywords: 650; Average run length; Binary data; Markov chain; Bernoulli CUSUM; Estimating process parameters